2008
DOI: 10.1002/fam.970
|View full text |Cite
|
Sign up to set email alerts
|

Hollow‐core concrete slabs exposed to fire

Abstract: SUMMARYThe aim of this paper is to provide recommendations to designers and to propose a simple method for designers to model the structural behaviour of hollow-core concrete (HC) floor slabs in fire. The proposed finite element model incorporates a grillage system using beam elements to capture the thermal expansion of the precast units in both directions, with the topping concrete over several precast units modelled by shell elements. The research reported herein compares the proposed model with various fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Nevertheless, the model considers the prestressing effect, the thermal strains as well as the mechanical stresses induced by incompatible thermal strains in both lateral and longitudinal directions, and the continuity between the hollowcore units which subsequently allows the model to take account of the effects of the end and side supports. Most importantly, the results from this modelling method showed good agreement with experimental results available in literature 4 . The model developed in the previous study worked well for small subassemblies.…”
Section: Modelling Of Hollowcore Slabs In Safirsupporting
confidence: 81%
See 3 more Smart Citations
“…Nevertheless, the model considers the prestressing effect, the thermal strains as well as the mechanical stresses induced by incompatible thermal strains in both lateral and longitudinal directions, and the continuity between the hollowcore units which subsequently allows the model to take account of the effects of the end and side supports. Most importantly, the results from this modelling method showed good agreement with experimental results available in literature 4 . The model developed in the previous study worked well for small subassemblies.…”
Section: Modelling Of Hollowcore Slabs In Safirsupporting
confidence: 81%
“…Chang et al 4 have showed that SAFIR can successfully predict the performance of hollowcore floor systems in fire by using a grillage of 3D beam elements to simulate the hollowcore units and a layer of shell elements to represent the topping concrete slab which covers the hollowcore units and connects the hollowcore units to each other and to the surrounding structural members.…”
Section: Modelling Of Hollowcore Slabs In Safirmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [11] have modelled the floor slabs with beam or shell elements whose end nodes share the nodes of the beam elements representing the supporting beams. This is acceptable for cast-in-situ or precast flooring system without prestressing, but leads to a major problem for precast prestressed flooring systems where the steel tendons terminate at the end of the flooring units, because the approach of sharing nodes of the supporting beam and floor assumes that these tendons are anchored into the supporting beams.…”
Section: Introductionmentioning
confidence: 99%